Visual Communication Strategy: The Effectiveness of Profile Videos in Increasing Awareness and Image of Religious Education Foundations: (A Case Study of Yusrotus Syafa’ah Al Yusfa Foundation) - Agus Wibowo; Khozinatus Sadah; Muhammad Irsadul Ibad (ISAS, 2026)
The Yusrotus Syafa’ah Al Yusfa Foundation is a religious educational institution focusing on Qur’anic and tahfidz learning. Despite its active educational programs, the foundation experiences limited public exposure due to the absence of professionally designed visual communication media. This study aims to design, develop, and evaluate the effectiveness of a profile video as a strategic visual communication tool to increase public awareness and strengthen the institutional image. This research employs a Design and Development (D&D) approach, consisting of needs analysis, narrative and visual design, audiovisual production, and user-based evaluation. The product is a 4-minute-46-second profile video emphasizing emotional storytelling, cinematic visuals, and authentic documentation of institutional activities. The effectiveness of the video was evaluated through a post-test questionnaire administered to 17 respondents using a five-point Likert scale. The results indicate a satisfaction level of 92.2% (Very Satisfied category) and show that 88.9% of respondents gained new knowledge about the foundation after watching the video. These findings demonstrate that the developed profile video is highly effective in improving public awareness, enhancing message clarity, and strengthening the positive image and credibility of the institution. The study confirms that systematically designed audiovisual media can function not only as promotional tools but also as strategic visual communication instruments for non-profit and religious educational organizations.